Changes of prominent vessel sign and susceptibility vessel sign in acute ischemic stroke patients with and without successful recanalization: a study based on susceptibility weighted images. (3rd July 2022) - Li, Zhiye; Bai, Xiaoyan; Gao, Peiyi; Lin, Yan; Ju, Yi; Sui, Binbin
ABSTRACT: Objectives: To investigate the changes of prominent vessel sign (PVS) and susceptibility vessel sign (SVS) in acute ischemic stroke (AIS) patients with successful and non-successful vascular recanalization treatment, and to study the associations between the susceptibility-weighted imaging (SWI) findings and early clinical and imaging prognosis. Methods: Thirty-five patients with the acute MCA territory infarction were retrospectively included and classified into Groupre (n = 25) and Groupnon (n = 10) according to the success of vascular recanalization. NIHSS was used for clinical assessment. PVS and DWI were analyzed using ASPECT scores. Baseline, post-treatment, the changes of PVS and SVS, and SVS length were recorded and compared between two groups. Correlation analysis was performed between SWI factors and early post-treatment clinical and imaging factors. Results: The mean PVSpre value was 5.20 ± 1.76 and PVSpost was 8.20 ± 1.86. PVSpre and PVSpost showed statistical significance between Groupre and Groupnon (both p < 0.001). A significant difference wasfound in SVSpost (+) ( p < 0.001), SVSpost-pre (+) ( p = 0.001), SVSpost-pre length (p = 0.036) and SVSpost length (p = 0.001) between the two groups. A positive correlation was found between PVSpre and DWIpost ( p < 0.001, r = 0.564). There were positive correlations between PVS-DWI mismatch and NIHSSpost in Groupre ( p = 0.042, r = 0.410) and in Groupnon ( p = 0.006, r = 0.789). Conclusions: PVS and SVS changes are influenced by the success of vascular recanalization. However, the changes are unrelated to either early clinical or imaging outcomes in AIS patients. PVS-DWI mismatch can be taken as an imaging biomarker for early clinical outcomes, both for patients with or without successful vascular recanalization.